Conjugate vaccines for enteric fever: proceedings of a meeting organized in New Delhi, India in 2009 - Audino Podda; Allan James Saul; Rashmi Arora; Zulfiqar Bhutta; Anju Sinha; Rajni Gaind; Tanu Singhal; Samir Saha; Abdullah Brooks; Laura B. Martin; Yeshwant Amdekar; Amar Jeet Chitkara; et al. (Journal of Infection in Developing Countries)
Enteric fever is responsible for significant morbidity in South Asia and high prevalence of severe disease is seen in children under two years of age. Effective typhoid vaccines are available, but they cannot be used for children under two years of age and also have some limitations in older age groups. Participants supported development of a Salmonella Typhi conjugate vaccine able to induce effective, long-lasting immunity in young children. The role of Salmonella Paratyphi A as a cause of enteric fever was discussed and consensus reached that a bivalent S. Typhi-S. Paratyphi A conjugate vaccine is highly desirable; however, considering disease epidemiology and the advanced status of vaccine development, rapid introduction of monovalent S. Typhi conjugate vaccine into vaccination programs of South Asia was recommended. Prevention should be emphasized, available vaccines used, and efforts toward improving sanitation continued.